Controlling the Emission Zone by Additives for Improved Light‐Emitting Electrochemical Cells. Issue 8 (15th January 2022) - Ràfols‐Ribé, Joan; Zhang, Xiaoying; Larsen, Christian; Lundberg, Petter; Lindh, E. Mattias; Mai, Cuc Thu; Mindemark, Jonas; Gracia‐Espino, Eduardo; Edman, Ludvig
Abstract: The position of the emission zone (EZ) in the active material of a light‐emitting electrochemical cell (LEC) has a profound influence on its performance because of microcavity effects and doping‐ and electrode‐induced quenching. Previous attempts of EZ control have focused on the two principal constituents in the active material—the organic semiconductor (OSC) and the mobile ions—but this study demonstrates that it is possible to effectively control the EZ position through the inclusion of an appropriate additive into the active material. More specifically, it is shown that a mere modification of the end group on an added neutral compound, which also functions as an ion transporter, results in a shifted EZ from close to the anode to the center of the active material, which translates into a 60% improvement of the power efficiency. This particular finding is rationalized by a lowering of the effective electron mobility of the OSC through specific additive: OSC interactions, but the more important generic conclusion is that it is possible to control the EZ position, and thereby the LEC performance, by the straightforward inclusion of an easily tuned additive in the active material. Abstract : The position of the in situ formed emission zone (EZ) in light‐emitting electrochemical cells has a profound influence on the device performance because of microcavity effects and doping and electrode quenching. This study shows that the inclusion of easily tuned additives can rationally shift the EZ position for improved performance.